Combination of drugs acting on the natriuretic system and the renin-angiotensin system in heart failure. - Chee, K.H.; Amudha, K.; Hussain, N.A.; Haizal, H.K.; Choy, Anna-Maria J.; Lang, C.C. (2003)
Conventional diuretic agents are very effective agents in relieving volume overload and congestive symptoms in chronic heart failure (CHF). However, they are associated with activation of the renin-angiotensin system (RAS) and the sympathetic nervous system and a reduction in glomerular filtration rate, all of which have been associated with adverse outcomes in CHF. Therefore, there is an increasing interest in drugs that target the natriuretic system without neurohormonal activation and deterioration of renal function. In this review, we will discuss the underlying rationale and evidence behind currently pursued strategies that target the natriuretic system. This includes the administration of natriuretic peptides (NPs) and strategies that potentiate the NP system, such as neutral endopeptidase inhibition. We will also highlight some potentially important interactions of these strategies with drugs that target the RAS.